Reversibility of Cardiac Involvement in Acromegaly Patients After Surgery: 12-Month Follow-up Using Cardiovascular Magnetic Resonance - Guo, Xiaopeng; Cao, Yihan; Cao, Jian; Li, Xiao; Liu, Peijun; Wang, Zihao; Gao, Lu; Bao, Xinjie; Xing, Bing; Wang, Yining (Frontiers in Endocrinology, 2020)
Purpose Cardiac comorbidity is one of the leading causes of death among acromegaly patients. We aimed to investigate the reversibility of acromegalic cardiac involvement after surgical treatment using the gold standard method, cardiovascular magnetic resonance, and to explore the effects of endocrine remission and gender on reversibility. Methods In this single-center, prospective cohort study, fifty untreated acromegaly patients were enrolled. Comprehensive cardiac assessments were performed using a 3.0 T magnetic resonance scanner before and 3 and 12 months after transsphenoidal adenomectomy. Results Preoperatively, left ventricular (LV) enlargement (13.0%), LV systolic dysfunction (6.5%), right ventricular (RV) enlargement (4.3%), RV systolic dysfunction (2.2%) and myocardial fibrosis (12.0%) were identified. On average, the LV and RV ejection fractions of acromegaly patients were higher than the healthy reference values. Male patients had thicker LV myocardia, wider ventricular diameters and more dilated pulmonary artery roots than female patients. After surgery, LV myocardial hypertrophy was reversed, the left atrium was remodeled, and ventricular systolic dysfunction recovered to normal. Cardiac alterations were detected early in the 3rd postoperative month and persisted until the 12th month. The interventricular septum was initially thickened in the 3rd postoperative month and then recovered at the 12th month. Notable postoperative cardiac reversibility was observed in male patients but did not occur in all female patients. Patients achieving endocrine remission with normalized hormone levels had thinner LV myocardia than patients without normalized hormone levels. Conclusion Our findings demonstrated that some of the cardiac involvement in acromegaly patients is reversible after surgical treatment which lowers hormone levels. Endocrine remission and gender significantly impacted postoperative cardiac reversibility.